Regioregularity and deposition effect on the physical/chemical properties of polythiophene derivatives films - Roncaselli, Lucas K.M. [UNESP] (2019)
Polythiophene thin films are widely studied for applications in organic electronics. However, some comparisons are still missing, regarding distinct deposition techniques and regioregularity. Here regioregular and regiorandom alkyl-substituted polythiophene derivatives (P3ATs) were deposited on solid substrates using both Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) techniques. The main goal was to verify the possible influence of the regioregularity as well the deposition technique on their optical, electrical and electrochemical properties. LB and LS films of regioregular and regiorandom poly(3-butylthiophene) (P3BT) and poly(3-octylthiophene) (P3OT) were deposited onto glass/Indium-Tin-Oxide) substrates and characterized by UV-visible optical spectroscopy, atomic force microscopy, cyclic voltammetry, and conductivity measurements. The results demonstrated the influence of the deposition technique on the electrical outcome, moreover, the regioregularity affected all the performed characterizations. In addition, this paper may be useful to understand how the amphiphilic molecule addition affected the film properties of regioregular and regiorandom P3ATs, particularly the energy diagram provided by the electrochemical and absorption features.